SHM_3266294_3D Vendel Fragment: Helmet Fragment with Ornamentation - Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a helmet fragment from the Vendel period with pressed-plate ornamentation. Excavated from Vendel Boat Grave XI/Boat Grave 11 in Vendel, Uppsala, it is currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collections platform

https://dyncoll.ht.lu.se/artifact_view.php?item=979

Link to Sök I Samlingarna

https://samlingar.shm.se/object/990c9715-0a19-42cf-a3f6-2ad8b2d7373e
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Photogrammetry; 3D Model; Museum Object; Dynamic Collections; Vendel; Vendel Period; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi